Amplification-free nucleic acid detection with a fluorescence-based waveguide biosensor - Kocheril, Philip A.; Lenz, Kiersten D.; Jacobsen, Daniel E.; Kubicek-Sutherland, Jessica Z. (Frontiers in Sensors, 2022)
Early detection of pathogens using nucleic acids in clinical samples often requires sensitivity at the single-copy level, which currently necessitates time-consuming and expensive nucleic acid amplification. Here, we describe (1) a redesigned flow cell in the shape of a trapezoid-subtracted geometric stadium, and (2) modified experimental procedures that allow for the measurement of sub-attomolar analytes in microliter quantities on a fluorescence-based waveguide biosensor. We verified our instrumental sensitivity with a 200-μL sample of a fluorescent streptavidin conjugate at 100 zM (100 zeptomolar, or 100·10–21 mol·L–1) and theoretically explored the applicability of this modified sensing platform in a sandwich immunoassay format using a Langmuir adsorption model. We present assays that demonstrate specific detection of synthetic influenza A DNA (in buffer) and RNA (in saliva) oligonucleotides at the single-copy level (200 μL at 10 zM) using a fluorescent molecular beacon. Lastly, we demonstrate detection of isolated genomic influenza A RNA at a clinically relevant concentration. This work constitutes a sensitivity improvement of over twelve orders of magnitude compared to our previous nucleic acid detection work, illustrating the significant enhancements that can be gained with optimized experimental design.